Crime During the Transition to Adulthood: How Youth Fare As They Leave Out-of-Home Care in Illinois, Iowa, and Wisconsin, 2002-2007 - Courtney, Mark E. ([Verlag nicht ermittelbar], 2010)
The purpose of the study was to examine criminal behavior and criminal justice system involvement among youth making the transition from out-of-home care to independent adulthood. The study collected data from two sources: (1) survey data from the Midwest Study of the Adult Functioning of Former Foster Youth (Midwest Study), and (2) official arrest data. The Midwest Study was a longitudinal panel study that was part of a collaborative effort of the state public child welfare agencies in Illinois, Iowa, and Wisconsin, Chapin Hall at the University of Chicago, and the University of Washington. The participating states funded and/or operated the full range of services supported by the Chafee Foster Care Independence Program. The Midwest Study survey data were collected directly from the youth in the sample every two years over three waves, between May 2002 and January 2007. A total of 732 respondents participated in at least one of the in-person interviews over the three waves. This data collection includes some variables that were directly measured from the original Midwest Study survey instrument and other variables that were computed or derived from variables in the original data for purposes of the current study. To supplement the survey data, the research team accessed official arrest data from each state for this study. Researchers obtained data on all criminal arrests that occurred between the respondents' Wave 1 interview and August 31, 2007, a date by which all of the study participants were at least 21 years old. The study contains a total of 85 variables including indicator variables, demographic and background variables, delinquency and crime variables, out-of-home care experiences variables, and social bonds variables.